2019
DOI: 10.4070/kcj.2018.0208
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Survival in Korean Elderly Patients with Symptomatic Severe Aortic Stenosis Who Refused Aortic Valve Replacement

Abstract: Background and ObjectivesAortic valve replacement (AVR) is the treatment of choice in severe symptomatic aortic stenosis (AS) patients. However, a substantial number of elderly patients refuse AVR and treated medically. We investigated their long-term prognosis.MethodsFrom January 2005 to December 2016, we analyzed elderly patients with severe symptomatic AS who refused to have AVR.ResultsAfter screening of total 534 patients, we analyzed total 180 severe symptomatic AS patients (78±7 years old, 96 males). Hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that the degree of anemia is associated with the degree of severity of aortic stenosis, and patients with severe aortic stenosis and severe anemia have a higher mortality rate [30,31]. Nagao et al assessed the impact of anemia on cardiovascular and bleeding outcomes in 3,403 patients enrolled in the CURRENT aortic stenosis registry, and they found that moderate and/or severe anemia was associated with a significantly increased risk for this primary outcome measure as well as for major bleeding [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the degree of anemia is associated with the degree of severity of aortic stenosis, and patients with severe aortic stenosis and severe anemia have a higher mortality rate [30,31]. Nagao et al assessed the impact of anemia on cardiovascular and bleeding outcomes in 3,403 patients enrolled in the CURRENT aortic stenosis registry, and they found that moderate and/or severe anemia was associated with a significantly increased risk for this primary outcome measure as well as for major bleeding [32].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing systemic vascular resistance and stiffness may also contribute to the vicious circle of DAS [6]. Once symptoms of DAS develop, life expectancy is shortened to around 3 years unless the mechanical obstruction to left ventricular outflow is relieved by aortic valve replacement [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This study found a lower mortality rate than previous studies did: one-year mortality rates ranged from 33.5% in one study of unoperated symptomatic severe AS patients,4) 38% in another study of unoperated severe AS patients,6) up to 50.7% in inoperable symptomatic severe AS patients in the Placement of Aortic Transcatheter Valves (PARTNER) trial 7). One main reason may be that the study by Oh et al5) enrolled the ‘younger’ elderly AS patients (78±7 years), whereas the mean age of AS patients enrolled in the PARTNER trial was 83.1±8.6 years. Since age itself is one of the most important unmodifiable risk factors of mortality, it seems that the study by Oh et al5) recruited AS patients at a somewhat lower risk.…”
mentioning
confidence: 47%
“…AS patients who could not undergo surgical correction for various reasons can now achieve longevity with greater quality of life through TAVR, and thus, the number of AS patients treated medically is expected to decrease. In this respect, the article given by Oh et al5) in this issue of the Korean Circulation Journal may seem to be outdated. Notwithstanding, we believe that this article is of value, because no data has hitherto been published regarding the portion of AS patients in Korea being treated medically.…”
mentioning
confidence: 99%
See 1 more Smart Citation